1999
DOI: 10.1111/j.1528-1157.1999.tb05568.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research Physical Exercise in Outpatients with Epilepsy

Abstract: EpilepsySummary: Purpo.se: To compare the exercise habits in a sample of adult outpatients with epilepsy with those of a general population of the same age and sex and furthermore to m d y physical exercise as a seizure precipitant and the risk of sustaining seizure-related injuries while exercising.Metlzods; Two hundred four adult outpatients with active epilepsy responded to two questionnaires. The first one, addressing exercise habits, was a selected part of a broad selfassessing screening used every secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
2
10

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(140 citation statements)
references
References 30 publications
6
122
2
10
Order By: Relevance
“…This finding of fear as an exercise deterrent is in accordance with current research [1,4,7,8,10,30,31], however, the qualitative approach taken allowed for the diverse ways in which fear manifested itself to be revealed. Such manifestation included the fear that seizures could prevent Maya from achieving her end goal and would cause teammates to keep away from Andrew at the gym, as well as create the feelings of a loss of independence for Rose and Gwen.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This finding of fear as an exercise deterrent is in accordance with current research [1,4,7,8,10,30,31], however, the qualitative approach taken allowed for the diverse ways in which fear manifested itself to be revealed. Such manifestation included the fear that seizures could prevent Maya from achieving her end goal and would cause teammates to keep away from Andrew at the gym, as well as create the feelings of a loss of independence for Rose and Gwen.…”
Section: Discussionsupporting
confidence: 88%
“…Medical advice in maintaining exercise habits differed amongst the participants and created a barrier to exercise. Although recommendations to continue exercise for emotional benefit are prevalent in current epilepsy and exercise literature [2,3,7,8,34,36,37], and were shown through recommendations to Rose and Gwen, it was interesting to witness the emotional effect of the differences in medical advice provided, as was shown through Andrew's narrative. This first-hand insight into advice provided by medical professionals as well as the support that is needed by people with epilepsy to maintain an exercise routine has yet to be presented within the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, seizures exacerbated by physical exercise are uncommon in humans 7,9,18 . one study 19 found that only 2% of patients with epilepsy had exercise-induced seizures (defined as seizures in >50% of training sessions). we also might suggest that in refractory epilepsy, the possibility of exercise to provoke seizure could be increase.…”
Section: Resultsmentioning
confidence: 99%